How do college students and kindergarten children draw the preferred dividing lines in rectangles? - Yogo, Yumi; Hama, Haruyo; Matsuyama, Yoshinori (Shinrigaku kenkyū, 1997)
Based on the study of Davis and Jahnke (1991), we examined preference of division ratios using a production method, in which subjects were asked to draw a horizontal or vertical dividing line on each stimulus figure. The subjects were sixty three college students and forty five kindergarten children. The stimulus figures were a square and six kinds of rectangles. The results revealed the following points: (1) For both college students and kindergarten children, the frequencies of the 1:1 dividing ratio (the unity ratio) were the highest. (2) For the college students, the shorter the side which the dividing line meets at right angles became, the stronger the preference to the unity ratio got. (3) For both the students and the children, the frequencies of the 1:1 dividing ratio for the square were the highest.